2021
DOI: 10.3390/nu13020393
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Hepcidin Levels with Aerobic and Resistance Exercise: A Systematic Review

Abstract: Background: Prevalence of iron deficiency is commonly reported among athletic population groups. It impairs physical performance due to insufficient oxygen delivery to target organs and low energy production. This is due to the high demand of exercise on oxygen delivery for systemic metabolism by the erythrocytes in the blood. Hepcidin, the key regulator of iron homeostasis, decreases to facilitate iron efflux into the circulation during enhanced erythropoiesis. However, acute anaemia of exercise is caused by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 64 publications
2
33
1
Order By: Relevance
“…Iron deficiency is associated with an alteration of the transport and delivery of oxygen to the tissues, and therefore may affect athletic performance. Iron is also involved in energy metabolism within the electron transport chain, DNA synthesis, oxidative phosphorylation in mitochondria, and ATP production [ 17 , 18 ]. Iron deficiency affects up to 52% of female adolescent athletes [ 6 ] and 30–50% of athletes participating in endurance sports [ 19 ].…”
Section: Iron Deficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Iron deficiency is associated with an alteration of the transport and delivery of oxygen to the tissues, and therefore may affect athletic performance. Iron is also involved in energy metabolism within the electron transport chain, DNA synthesis, oxidative phosphorylation in mitochondria, and ATP production [ 17 , 18 ]. Iron deficiency affects up to 52% of female adolescent athletes [ 6 ] and 30–50% of athletes participating in endurance sports [ 19 ].…”
Section: Iron Deficiencymentioning
confidence: 99%
“…The iron metabolism involves absorption from the duodenal enterocytes, usage in the erythroid precursors, and storage and reutilization in the hepatocytes and tissue macrophages ( Figure 1 ) [ 19 ]. Hepcidin is the key regulator of iron homeostasis, as its synthesis is inhibited to facilitate iron efflux in the circulation during increased erythropoiesis [ 17 ]. Hepcidin is produced in the liver and degrades the ferroportin transport channel, reducing the ability of macrophages to recycle the iron and thus iron availability [ 22 ].…”
Section: Iron Deficiencymentioning
confidence: 99%
“…Recently, many researchers have attempted to find a biomarker for exercise-induced anemia, and the hepcidin level was suggested as a potential biomarker for lower energy availability [ 8 , 13 , 16 , 17 ]. It is well known that the hepcidin level is positively correlated with the ferritin level [ 13 , 14 , 15 , 16 ]. In the present study, we confirmed this relationship in male university rugby players.…”
Section: Discussionmentioning
confidence: 99%
“…However, normal hepcidin levels among athletes remain a topic of debate [ 11 , 12 ]; while one study shows that the levels are higher in athletes [ 11 ], another reports that the levels are not elevated [ 12 ]. This discrepancy is partly ascribed to the fact that lean athletes have low ferritin levels, and resting hepcidin levels are generally regulated by the ferritin level [ 13 , 14 , 15 , 16 ]; however, in some cases, the hepcidin level is independent of the ferritin level. For instance, acute exercise increases the hepcidin level without changing the ferritin level due to exercise-induced inflammation caused by elevated interleukin-6 (IL-6) levels [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation